Adherence to Antidiabetic Medications among Women with Gestational Diabetes. (6th August 2021) - Asiedu-Danso, Michelle; Kretchy, Irene A.; Sekyi, Jeremiah Kobby; Koduah, Augustina
Abstract : Background . Optimal adherence to prescribed medications in women with gestational diabetes is relevant for perinatal outcomes. Objective . To summarize available information on the prevalence and factors contributing to medication adherence in women with gestational diabetes from the biological and psychosocial perspectives. Methods . A literature search on adherence in gestational diabetes was conducted in PubMed/MEDLINE, CINAHL, Scopus, and the Directory of Open Access Journals for studies published on the topic. The Arksey and O'Malley framework for scoping reviews was used to explore and summarize the evidence. Results . A total of 2395 studies were retrieved of which 13 fully met the eligibility criteria. The studies were reported in Zimbabwe (n = 5 ), Iran (n = 1 ), Mexico (n = 1 ), South India (n = 1 ), the United States of America (n = 4 ), and one multinational study covering Australia, Europe, North and South America. The main types of antidiabetic medications used were insulin (n = 6 ), metformin (n = 4 ), and glyburide (n = 2 ). The prevalence of adherence ranged from 35.6% to 97%, with the assessment tool being self-report measures (n = 8 ). The main factors associated with nonadherence included worsening pregnancy symptoms, side effects of medications, perceived risks, mental health symptoms, poor social support, and socioeconomic status. Recommendations that evolved from the studies to improve adherence included education, counselling, improved support networks, and social interventions, while the main reported interventional study employed continuous education on the impact of adherence on perinatal outcomes. Conclusion . Medication nonadherence in gestational diabetes seems to be influenced by multiple factors with some educational interventions positively impacting adherence behaviours. Thus, future research in women with gestational diabetes could consider interventions from a multifactorial perspective to improve therapeutic outcomes.